The effect of financial reporting quality and debt maturity on investment efficiency - seyed Abbas Hashemi; Saeed Samadi; Reyhaneh Hadian (مطالعات تجربی حسابداری مالی, 2015)
In current business world, companies require suitable strategies forbetter use of their resources and wealth to solve their economicproblems. For this goal, one way is development of investment. Inaddition to development of investment, the efficiency of investment isso important. Hence, this study examines the effect of financialreporting quality and debt maturity on investment efficiency. for dataanalysis and Hypothesis testing the multiple regressions models wasused .This research has been done in 104 listed companies in TehranStock Exchange based on data contained in financial reports between2007 – 2012. The results show that upper financial reporting qualityand lower debt maturity can improve investment efficiency .resultsalso show firms with higher (lower) use of short-term debt, exhibitlower (higher) financial reporting quality effect on investmentefficiency. In other world, financial reporting quality and debtmaturity are mechanisms with some degree of substitution inenhancing investment efficiency.